Sarazen: The Story of a Golfing Legend and His Epic Moment - Sowell, David (Rowman & Littlefield Publishers, 2017)
Bobby Jones and Tiger Woods won their first majors at the age of 21. Jack Nicklaus and Jordan Spieth claimed their first majors at the age of 22. By the time he was 21, Gene Sarazen had won three. Considered one of the top golfers in the 1920s and ’30s, he is one of only a handful of golfers to win all the major championships—the U.S. Open, the PGA Championship, the Open Championship, and the Masters Tournament. Sarazen: The Story of a Golfing Legend and His Epic Moment details Sarazen’s life and storied career, from his days sweeping floors in a pro shop through his rise in the golfing world to become one of the country’s foremost players. Central to the story is Sarazen’s iconic moment in the sport, a long shot from 235 yards that somehow found the bottom of the cup at Augusta National—perhaps fitting for a man whose golfing career was once considered a long shot itself. It became the greatest shot in golf history and put the Augusta National Golf Club on the map. Sarazen offers an in-depth look at a golfing legend and provides a fascinating glimpse into the world of golf during a time when the game was still rising in prominence. Rich in detail and including many little-known anecdotes, this book will be enjoyed by golfing enthusiasts and historians across generations.